Identification of the natural breeding sites of sandflies (Diptera : Psychodidae : Phlebotominae), potential vectors of leishmaniasis, in the province of Chaco, Argentina - Parras, Matías Ariel (2012)
Fil: Parras, Matías Daniel. Universidad Nacional del Nordeste. Instituto de Medicina Regional; Argentina.